Deep sequencing of short RNAs reveals novel microRNAs in minor salivary glands of patients with Sjögren’s syndrome - Tandon, M (2011)
OBJECTIVES: Sjögren’s syndrome is a complex autoimmune disease of the salivary gland with an unknown etiology, so a thorough characterization of the transcriptome would facilitate our understanding of the disease. We use ultradeep sequencing of small RNAs from patients with Sjögren’s syndrome and healthy volunteers, primarily to identify and discover novel miRNA sequences that may play a role in the disease. METHODS: Total RNA was isolated from minor salivary glands of healthy volunteers and patients with either high or low salivary flow and sequenced on the SOLiD platform. Prediction of mature miRNAs from the sequenced reads was carried out using miRanalyzer, and expression was validated using Taqman qPCR assays. RESULTS: We validated the presence of six previously unidentified miRNA sequences in patient samples and in several cell lines. One of the validated novel miRNAs shows promise as a biomarker for salivary function. CONCLUSION: Sequencing small RNAs in the salivary gland is largely unprecedented, but here, we show the feasibility of discovering novel miRNAs and disease biomarkers by sequencing the transcriptome.